NÚÑEZ, Amanda (2019). Gilles Deleuze. Una estética del espacio para una ontología menor. Madrid: Arena Libros, 232 págs. - Jiménez Asensio, Rosa (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: NÚÑEZ, Amanda (2019). Gilles Deleuze. Una estética del espacio para una ontología menor. Madrid: Arena Libros.